Indirect effect of diabatic heating on Mei-yu frontogenesis - Yang Hu; Yi Deng; Yanluan Lin; Zhimin Zhou; Chunguang Cui; Chao Li; Xiquan Dong (Climate Dynamics, 2022)

Dynamics of the spatiotemporal morphology of Mei-yu fronts: an initial survey - Yang Hu; Yi Deng; Yanluan Lin; Zhimin Zhou; Chunguang Cui; Xiquan Dong (Climate Dynamics, 2021)
Mei-yu fronts are often accompanied with prominent diabatic heating due to the development of frontal clouds and rain bands. The direct effect and relative importance of diabatic heating on the spatiotemporal morphology of Mei-yu fronts however remain unclear. Here a new frontogenesis function is derived to isolate the effect of diabatic heating and this function is then applied to the latest high resolution reanalysis product ERA5 to conduct an initial survey of dynamic and thermodynamic processes driving the intensity and structure evolutions of three typical Mei-yu fronts. It is found that the direct effect of latent heating (moisture depletion) is always frontogenetical (frontolytical) in the pre-frontal and frontal zone throughout the lifecycle of the front with latent heating (moisture depletion) in general dominates the front intensification (dissipation). Tilting is another critical process that turns the vertical gradient of equivalent potential temperature into horizontal gradient leading to frontogenesis during the front development stage, and, after the release of convective instability ahead of the front, flattens the front surface leading to frontolysis during the front decaying stage. Therefore titling maintains consistently positive contributions to the evolution of a Mei-yu front and its importance depends highly on the convective intensity near the front. The deformation effect appears frontogenetical but carries a much smaller weight compared to diabatic heating, moisture depletion and tilting. The structure evolutions of the three Mei-yu fronts studied here exhibit two distinct patterns: “bending and breaking”, and “moving and rotating”. Both patterns are dominated by the front propagation (i.e., frontogenesis through air parcels), further highlighting the critical roles played by diabatic heating, moisture depletion and titling in determining the spatiotemporal characteristics of Mei-yu fronts. As these three processes are all closely tied to updrafts, clouds and precipitation near the fronts, improved representations of clouds and convection are needed to accurately depict their feedbacks to frontal evolutions and ultimately achieve better predictions of heavy rainfall and floods associated with Mei-yu fronts.